Essential hazard and process safety assessment of para-toluene sulfonic acid through calorimetry and advanced thermokinetics. (September 2021) - Huang, An-Chi; Li, Zhi-Ping; Liu, Ye-Cheng; Tang, Yan; Huang, Chung-Fu; Shu, Chi-Min; Xing, Zhi-Xiang; Jiang, Jun-Cheng
Abstract: Para-toluene sulfonic acid is a typical intermediary for the synthesis of pharmaceuticals, pesticides, and dyes and is a catalyst for organic synthesis. The consumption of para-toluene sulfonic acid used in organic synthesis has increased substantially. The toluene sulfonation process is the central path for synthesizing para-toluene sulfonic acid in China. However, the process has risks and has resulted in numerous disasters. This study utilized a reaction calorimeter 1 to reproduce the commercial toluene sulfonation process in a laboratory. The para-toluene sulfonic acid product was examined with an accelerating rate calorimeter and through differential scanning calorimetry. Both differential and integral isoconversional methods were used to determine the thermal stability of and appropriate thermokinetic models for para-toluene sulfonic acid. The safety parameters of para-toluene sulfonic acid were estimated. The research findings can be used for optimization of the toluene sulfonation process and for safe handling of para-toluene sulfonic acid. Highlights: The thermal hazards of toluene sulfonation process and its product were scrutinized. Key parameters for safety diagram were calculated. The SADT values of para-toluene sulfonic acid was determined. Different isoconversional methods were used to evaluate and expound the thermal stability of para-toluene sulfonic acid.